Hard Work Will Bear Beautiful Fruit. A Comparison of Two Think-Aloud Protocol Studies - Jääskeläinen, Riitta (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1996)
AbstractIn this article some of the results of two think-aloud protocol studies (Gerloff 1988 and Jââskelâinen 1990) are compared. The purpose of the comparison is to illustrate two findings: (I) that translation does not always get easier as professional experience increases, and (2) that professional translators do not always succeed better than non-professionals. The emphasis is on these somewhat disturbing observations because they are particularly suitable for illustrating tentative hypotheses about the role of affective factors in translation. These, in turn, have important implications for teaching translation.